SOGDIAN LANGUAGE AS AN ECONOMIC, SOCIAL AND CULTURAL INTEGRATIVE FACTOR IN CENTRAL ASIA AND ALONG THE GREAT SILK ROAD - Sattorov Eldor Bobir o‘g‘li (International Journal of Literature and Language Studies, 2026)
Abstract: This article examines the Sogdian language as an economic, social and cultural integrative factor in Central Asia and along the Great Silk Road. The study argues that Sogdian functioned not only as a local language of an Iranian-speaking people of Transoxiana, but also as a practical medium of commercial documentation, caravan communication, religious translation, diplomatic contact and intercultural exchange. Special attention is paid to the Sogdian merchant diaspora, the written tradition of Sogdian, and its mediating role in the cities and oasis networks that connected Samarkand, Bukhara, Panjikent, Turfan, Dunhuang and other centers of Eurasian interaction.